2017
DOI: 10.1186/s12934-017-0671-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved curdlan production with discarded bottom parts of Asparagus spear

Abstract: BackgroundThis work evaluated the improvement of curdlan production of Agrobacterium sp. ATCC 31749 by using culture medium containing juice of discarded bottom part of green Asparagus spear (MJDA). Curdlan production was carried out using Agrobacterium sp. ATCC 31749 in flasks with different volumes of MJDA and its non-juice-adding control (CK) incubated in shaker at 30 °C, 200 rpm rotation for 168 h.ResultsAll MJDA media increased Agrobacterium sp. ATCC 31749 cell mass and enhanced the cells’ ability to util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…It was concluded that cassava starch waste hydrolysate could serve as a substitute for glucose as a carbon source which could lower the production cost of curdlan [24]. The juice extracted from the discarded bottom part of asparagus spears was investigated for its possible use as a supplement to support curdlan production by ATCC 31749 in a sucrose-containing medium [45]. When the 10% juice was added to the sucrose-containing culture medium, ATCC 31749 produced 40.2 g/L curdlan after 168 h of growth at 30 • C [45].…”
Section: Curdlan Production By Agrobacterium Strains Grown On Processmentioning
confidence: 99%
See 3 more Smart Citations
“…It was concluded that cassava starch waste hydrolysate could serve as a substitute for glucose as a carbon source which could lower the production cost of curdlan [24]. The juice extracted from the discarded bottom part of asparagus spears was investigated for its possible use as a supplement to support curdlan production by ATCC 31749 in a sucrose-containing medium [45]. When the 10% juice was added to the sucrose-containing culture medium, ATCC 31749 produced 40.2 g/L curdlan after 168 h of growth at 30 • C [45].…”
Section: Curdlan Production By Agrobacterium Strains Grown On Processmentioning
confidence: 99%
“…The juice extracted from the discarded bottom part of asparagus spears was investigated for its possible use as a supplement to support curdlan production by ATCC 31749 in a sucrose-containing medium [45]. When the 10% juice was added to the sucrose-containing culture medium, ATCC 31749 produced 40.2 g/L curdlan after 168 h of growth at 30 • C [45]. The juice supplement was found to support a higher level of curdlan production by ATCC 31749 compared to when the strain was grown in the sucrose-containing medium alone [45].…”
Section: Curdlan Production By Agrobacterium Strains Grown On Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The inoculated flasks were kept for shaking incubation at room temperature for 76 h at 180 rpm. The extraction of curdlan was done by centrifuging the culture medium at 12,000 × g for 30 min 17,18 . The extracted pellet was mixed with the same ratio of 0.5N Sodium hydroxide at 4 ºC.…”
Section: Seed Culture Preparation Production and Extraction Of Curdlanmentioning
confidence: 99%